Curious : the desire to know and why your future depends on it - Leslie, Ian, 1972- (Basic Books, A Member of the Perseus Books Group, 2014)
"Today it seems we have the world at our fingertips. Thanks to smartphones and tools such as Google and Wikipedia, we're able feed any aspect of our curiosity instantly. But does this mean we are actually becoming more curious? Absolutely not. In Curious, Ian Leslie argues that true curiosity-the sustained quest for understanding that begets insight and innovation-is becoming increasingly difficult to harness in our wired world. We confuse ease of access to information with curiosity, and risk losing our ability to ask questions that extend our knowledge gap rather than merely filling it. Worst of all, this decline in curiosity has led to a decline in empathy and our ability to care about those around us. Combining the latest science with an urgent call to cultivate curious minds, Curious draws on psychology, social history, and popular culture to show that being deeply curious is our only hope when it comes to solving current crises-as well as an essential part of being human. "--